A política de um esquecimento : a história de Japam e as disputas pelo poder e pela memória da missão jesuíta no Extremo Oriente (1578 -1602) - Santos, Cassianna Inês Geremias dos (2014)
In this work, we will analyse the writings of Father Luis Fróis, a Jesuit who was present in Japan during the 16th century and wrote about the development of the mission of the Society of Jesus in that territory fromt the the year 1549 to 1594, in his greatest work, Historia of Japam. This is a historiographical narrative about the presence, contacts, and activities of the missionary priests, as well as describes the main cultural events and Japanese politics. Despite being an official, and a text with a rich narrative scope, the work of Father Fróis was marginalized by the Jesuits and fell down into oblivion. In this research, we articulate the context and the main actors involved in the fate of the Historia de Japam. Our analyzes are based on the hypothesis that texto elaboreted by Fahter Fróis was characterized as an “open narrative” about the practices of evangelism and, as such, became incompatible with the restructuring plans of the eastern mission deployed by the Visitor of the Order, Father Alexander Valignano, in the 1580s . Such a contradiction caused the marginalization of the text compounded by Luiz Fróis. Therefore, this fate must be seen as an institutional phenomenon created by a political conflict. Over the five volumes of the Historia de Japam are reported episodes in which the priests of the Society of Jesus, famous for its accuracy and Tridentine obedience, lead a regular negotiation of the Catholic theology, involving practices bigamy, sodomy, preaching and rituals. The displacement of the doctrinal issues to the background of the history of the eastern mission exposed the policy of cultural accommodation designed by the Valignano to unacceptable risks, especially in the view of the European superiors. Our main methodology is the selection and discursive analysis of several passages of the Historia de Japam about the years 1549-1568. Those passages will be problematized in their rhetoric and doctrinal implications, and than confronted with the context of the clash between Fróis and Valignano. The methodology will be guided by the use of the concepts of “memory”, “open narrative” and “symbolic classification” sought in Walter Benjamin and Pierre Bourdieu.